In China, customer engagement mediates between brand image and purchase intention of premium hotels - Hoo, Wong Chee; Xiaoyan, Liu; Ziyae, Babak; Ramli, Suriana; Moosa, Visal (International Journal of Management and Sustainability, 2023)
The objective of this research is to investigate the relationship between the brand image of premium hotels in China, the level of customer engagement they experience, and their intention to make a purchase at one of those hotels. The study model that was developed made use of something called the Theory of Planned Behavior (TPB). Using a method known as convenience sampling, samples were collected from people living in Beijing, China. Participants in the poll who intended to make reservations at upmarket hotels were given the survey questionnaires. A grand number of 459 specimens were collected for the purpose of analysis. The process of data analysis and validation of the research hypotheses was conducted using SmartPLS. This research provides evidence that there is a connection between customer engagement and brand image, as well as the purchase intention. According to the findings of the study, the relationship between a brand’s image and a consumer’s propensity to make a purchase is diminished when customer engagement and brand image factors are both present. As a result, the efficacy of customer interaction as a mediator was shown to have been demonstrated. The academician is presented with new information in the form of this result, and further discussion is given regarding its application to practitioners.